„Discors concordia“ XVII a. jėzuitų kūryboje: teorinės prielaidos ir raiška - Daukšienė, Ona (Literatūra, 2015)
The paper deals with the theory of epigrammatic style as determined by M.C. Sarbievius (Sarbiewski, 1595–1640) in terms of concors discordia seu discors concordia in his treatise De acuto et arguto, sive Seneca et Martialis. These terms are analysed in the article not as a mere concept of acute style but as a verbal definition of the universal world understanding typical to baroque age as well. The focus is on the use of definitions concors discordia, discors concordia by the classical authors (Ovide, Horace, Manilius) in the context related with the world creation and structure; the theological dimension of these terms seems to be traceable in the poetry of early Christian poet Paulin of Nola and medieval authors. The analysis of different 17th century Jesuit Latin texts, especially of those dealing with the subject-matter related with the Church Union and the problems caused by this historical phenomenon reveals theconcors discordia seu discors concordia formula as fitting to Jesuitical discourse expressing the complexities of the multiform culture of Grand Duchy of Lithuania.